2017
DOI: 10.1177/1469066717717610
|View full text |Cite
|
Sign up to set email alerts
|

Label-free study of cosmonaut's urinary proteome changes after long-duration spaceflights

Abstract: During the entire time that cosmonauts stay on board the international space station, different extreme space flight factors affect their bodies. In order to find out what physiological changes occur under the influence of spaceflight, different parameters of the human body before and after flights are monitored. Analysis of the urine proteome is one of the most perspective non-invasive methods of condition monitoring. The aim of the study was to perform a comparative semi-quantitative label-free urine proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Previously we showed that overexpression of stress- or stimulus-associated proteins can be detected in urine on the 1st day after landing [13]. Most of the urine significant proteins that are associated with stress factors returns to its preflight levels up to the 7th day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we showed that overexpression of stress- or stimulus-associated proteins can be detected in urine on the 1st day after landing [13]. Most of the urine significant proteins that are associated with stress factors returns to its preflight levels up to the 7th day.…”
Section: Resultsmentioning
confidence: 99%
“…Blood and urine are the primary traditional subjects for the screening of physiological changes associated both with various diseases, and with extreme conditions or environmental factors [13,14]. However, the proteome of these samples collected in space cannot be analyzed in short time, and long-term storage significantly reduces their nativeness.…”
Section: Introductionmentioning
confidence: 99%
“…The main concerns with radiation are pathological vascular changes, genetic mutations, immune dysfunction, and cancer 4 , 5 , 10 . Epidemiological studies have suggested a latent relationship between radiation exposure and cardiovascular disease, 6–9 as well as with clonal hematopoiesis, 11 and physiologic studies in mice have shown long-lasting changes in cardiomyocyte gene expression and cellular signaling.…”
Section: Spaceflight Hazard: Radiationmentioning
confidence: 99%
“…Renal proteins serving as biomarkers of electrolyte regulation were altered, likely because of the fluid shifts that occur, overall decrease in plasma volume, and increased intake of salt additives. One study examining astronaut urinary proteome found that three proteins, glucosidase alpha acid (GAA), heparan sulfate proteoglycan (HSPG2), and alanyl aminopeptidase (ANPEP), do not return to baseline levels post-spaceflight, possibly correlating to changes in cytoskeletal reorganization, angiogenesis, extracellular matrix reorganization, and some features of hormone metabolism 5 . Additional proteomic changes that have been detected include increased production of cytokines (and cortisol), 22 changes in regulators of aerobic metabolism, and decrease in muscle and bone protein metabolism 18 , 23 …”
Section: Spaceflight Hazard: Gravitymentioning
confidence: 99%
“…Functional analysis of identified protein biomarkers highlighted many molecules contributing to vascular rigidity. Interested reader should also peruse the previous studies published by the same group, which also investigated the changes in urine proteome detected after spaceflight [14, 15].…”
mentioning
confidence: 99%